Elucidating the molecular mechanisms mediating plant salt-stress responses - Yang, Yongqing; Guo, Yan (The New phytologist, 2018)
Excess soluble salts in soil (saline soils) are harmful to most plants. Salt imposes osmotic, ionic, and secondary stresses on plants. Over the past two decades, many determinants of salt tolerance and their regulatory mechanisms have been identified and characterized using molecular genetics and genomics approaches. This review describes recent progress in deciphering the mechanisms controlling ion homeostasis, cell activity responses, and epigenetic regulation in plants under salt stress. Finally, wehighlight research areas that require further research to reveal new determinants of salt tolerance in plants.